Industrial agent technology - Bratukhin, Aleksey (2011)
The conventional centralized, rigid information systems cannot serve the demands of modern (manufacturing) industry adequately any longer. In order to stay competitive, industry needs to be highly flexible, with shorter job sizes, variable product portfolios, and always changing shop floors. Although centralized approaches can in the meantime provide highly sophisticated and efficient scheduling solutions, the requirements imposed by novel manufacturing trends renders centralized control systems more and more unfeasible (cf. [8]). Against this background, multi-agent based industrial information systems seem to be a promising and natural alternative. They provide decentralized architecture, modularity, robustness, and adaptability to changes (cf. [9]). Moreover, the evolution of industry in the previous decades has rearranged the principal goals, especially in manufacturing control. In the past, the main objective was achieving an optimal scheduling algorithm.